The impact of the use of focused reading strategies for the improvement of b2 level english students reading comprehension performance at the Foreigh Language Department at the University of El Salvador - Vásquez Cerón, Roxana Elizabeth
Reading in a foreign language plays a major role in improving the understanding and interpretation of texts and expanding vocabulary. Thanks to the reading, students review the sounds and spelling, vocabulary and grammar, fixed spelling and meaning of words and sentences and generally improve communicative competence in the foreign language. In this sense, the implementation of the different focused reading strategies is very important in the teaching-learning process because with this teacher guides students to perform better reading comprehension and language acquisition, also students will have the confidence to utilize these strategies on their own. The purpose of this study was to find out the impact of implementation of focused reading strategies in the performance B2 level English students of the Foreign Language Department at the University of El Salvador